One-pot synthesis of trifunctional chitosan-EDTA-β-cyclodextrin polymer for simultaneous removal of metals and organic micropollutants. Issue 1 (December 2017) - Zhao, Feiping; Repo, Eveliina; Yin, Dulin; Chen, Li; Kalliola, Simo; Tang, Juntao; Iakovleva, Evgenia; Tam, Kam; Sillanpää, Mika
Abstract The global contamination of water resources with inorganic and organic micropollutants, such as metals and pharmaceuticals, poses a critical threat to the environment and human health. Herein, we report on a bio-derived chitosan-EDTA-β-cyclodextrin (CS-ED-CD) trifunctional adsorbent fabricated via a facile and green one-pot synthesis method using EDTA as a cross-linker, for the adsorption of toxic metals and organic micropollutants from wastewater. In this system, chitosan chain is considered as the backbone, and the immobilized cyclodextrin cavities capture the organic compounds via host-guest inclusion complexation, while EDTA-groups complex metals. The thoroughly characterized CS-ED-CD was employed for batch adsorption experiments. The adsorbent displayed a monolayer adsorption capacity of 0.803, 1.258 mmol g−1 for Pb(II) and Cd(II) respectively, while a heterogeneous sorption capacity of 0.177, 0.142, 0.203, 0.149 mmol g−1 for bisphenol-S, ciprofloxacin, procaine, and imipramine, respectively. The adsorption mechanism was verified by FT-IR and elemental mapping. Importantly, the adsorbent perform is effective in the simultaneous removal of metals and organic pollutants at environmentally relevant concentrations. All these findings demonstrate the promise of CS-ED-CD for practical applications in the treatment of micropollutants. This work adds a new insight to design and preparation of efficient trifunctional adsorbents from sustainable materials for water purification.